Creative use of objects as signs in cinema: an analysis of Sergei Parajanov’s Hakob Hovnatanyan - Simyan, Tigran (Creativity Studies, 2024)
The paper presents an analysis of Sergei Parajanov’s short film, Hakob Hovnatanyan (1967), and its significance as an example of poetic cinema within Soviet cinematography. Not only feature-length films of Parajanov, but also his short films hold an important place among his œuvre, as a multi-modal and multi-channel visualization of the past. Hakob Hovnatanyan is a prime example of poetic cinema in Soviet cinematography. A pioneer in this discourse in the Soviet Union was Andrei Tarkovsky with his film Andrei Rublev (1966). Examples of this discourse include the Parajanov’s films The Color of Pomegranates (orig. Nṙan gowynë, 1969), Arabesque on a Theme of Pirosmani (orig. Arabeskebi Pirosmanis temaze, 1985), and Etudes on Vrubel (orig. Etyudy on Vrubel, 1989), which was directed by Leonid Osyka (scriptwriter Parajanov). The paper explores Hakob Hovnatanyan as a converter of cultural memory and multimodal vehicle for the construction of the spirit of the city. While in the framework of the short film the city is presented in the open air, in the middle the interior, the everyday life, the hum of language, and the language of clothes and necklaces of Old Tbilisi, Georgia, are presented. The interior and spirit are presented not only on the visual level of paintings, carpets, and furniture (a dresser with a metronome) but also through auditory elements: sound, language, music, etc. Thus, through a multimodal visualization of the past Parajanov presents a new language of cinema (Shadows of Forgotten Ancestors (orig. Tini zabutykh predkiv, 1965), The Color of Pomegranates, The Legend of Suram Fortress (orig. Ambavi suramis tsikhisa, 1985), Ashik Kerib (orig. Ashik’-keribi, 1988, first director Dodo Abashidze)).